Cardiac wall mechanics analysis in hypertension-induced heart failure rats with preserved ejection fraction. (2nd January 2020) - Yin, Zhongjie; Zhang, Wenxi; Zhao, Dongliang; Sulejmani, Fatiesa; Feng, Yundi; Huo, Yunlong; Tan, Wenchang
Abstract: Although cardiac wall mechanics is of importance for understanding heart failure with preserved ejection fraction (HFpEF), there is a lack of relevant mechanics studies. The aim of this study was to analyze the changes in stress and strain in the left ventricle (LV) in hypertension-induced HFpEF rats. Based on experimental measurements in DSS rats fed with high-salt (HS) and low-salt (LS) diets, LV stress and strain were computed throughout the cardiac cycle using Continuity software. HS-feeding increased myofiber stress and strain along both the transmural and longitudinal directions at the end-diastolic state but resulted in a lower absolute value of strain and relatively unchanged stress at the end-systolic state. Moreover, the end-diastolic stress and strain decreased with increasing radial position from the endocardial towards the epicardial walls despite negligible changes along the longitudinal direction. The changes in LV wall mechanics characterized the elevated diastolic LV stiffness and slow LV relaxation in HS-fed rats of HFpEF. These findings denote that a vicious cycle of increased stress and strain and diastolic dysfunction can prompt the development of HFpEF.